Distribution, partitioning behavior and positive matrix factorization-based source analysis of legacy and emerging polyfluorinated alkyl substances in the dissolved phase, surface sediment and suspended particulate matter around coastal areas of Bohai Bay, China. (March 2019) - Liu, Yunqing; Zhang, Ying; Li, Jiafu; Wu, Nan; Li, Wenpeng; Niu, Zhiguang
Abstract: The concentrations and spatial occurrences of 17 legacy per- and polyfluoroalkyl substances (PFAS) and 4 emerging PFAS in the coastal water-dissolved phase, surface sediment phase and suspended particulate matter (SPM) in the coastal areas of Bohai Bay were investigated. In addition, the partition behaviors of PFAS in the water-SPM system and water-sediment system and the potential sources of PFAS in the marine environment were revealed. The total concentrations of PFAS (∑PFAS) in the water-dissolved phase, surface sediment and SPM were 20.5–684 ng/L, 2.69–25.0 ng/g dry weight (dw) and 4.39–527 ng/g dw, respectively. The level of PFAS contamination in the coastal areas of Shandong Province was higher than that in other areas. The average partition coefficients (log Kd ) of PFAS in the water-SPM system and water-sediment system were 1.56–3.57 and 0.72–2.95, respectively. Long-chain PFAS and PFECHS (perfluoroethylcyclohexane sulfonate) have a higher log Kd than that of short-chain PFAS. PFAS with short carbon chains were mainly detected in the water-dissolved phase, but long-chain PFAS mainly occurred in the surface sediment and SPM phases. Source analysis based on the positive matrix factorization (PMF) model found that erosion inhibitor factories, aqueous film-forming foam factories, metal plating plants, fluoropolymer chemical manufacture and food contact materials were the main sources of PFAS in Bohai Bay. These results improved our understanding of the partitioning behavior and sources of PFAS in aquatic environments. Graphical abstract: ∑PFAS (ng/L) and composition profile in water dissolved phase in the coastal area of Bohai bay, China. Image 1 Highlights: Occurrences and sources of PFAS in water, surface sediment and SPM of Bohai bay were investigated. HFPO-DA and Cl-PFAESs were ubiquitous in water dissolved phase. Short-chain PFAS were mostly presented in water, while long-chain PFAS prevailed in sediment and SPM. AFFFs factories, metal plating plants, FP manufacture and food contact materials are the key contributing to PFAS. Abstract : The occurrence, partition behaviors and potential source of legacy and emerging PFAS in coastal areas were investigated.